2020 23rd Euromicro Conference on Digital System Design (DSD) 2020
DOI: 10.1109/dsd51259.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sensitivity of RRAM Cells to Optical Fault Injection Attacks

Abstract: Resistive Random Access Memory (RRAM) is a type of Non-Volatile Memory (NVM). In this paper we investigate the sensitivity of the TiN/Ti/Al:HfO2/TiN-based 1T-1R RRAM cells implemented in a 250 nm CMOS IHP technology to the laser irradiation in detail. Experimental results show the feasibility to influence the state of the cells under laser irradiation, i.e. successful optical Fault Injection. We focus on the selection of the parameters of the laser station and their influence on the success of optical Fault In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…[206,207] Theoretical studies have shown that Al-doped HfO x -based RSM layers are non-stoichiometric after sputtering, oxidation, and ion implantation. [208,209] However, atomic layer deposition results in enhanced chemistry. Utilizing ab initio calculations, recent studies have investigated the charge state, formation energy, and migration barrier of oxygen vacancies in four high-dielectricconstant oxides, i.e., TiO 2 , Al 2 O 3 , Ta 2 O 3 , and HfO 2 .…”
Section: Materials Selection and Experimental Guidancementioning
confidence: 99%
“…[206,207] Theoretical studies have shown that Al-doped HfO x -based RSM layers are non-stoichiometric after sputtering, oxidation, and ion implantation. [208,209] However, atomic layer deposition results in enhanced chemistry. Utilizing ab initio calculations, recent studies have investigated the charge state, formation energy, and migration barrier of oxygen vacancies in four high-dielectricconstant oxides, i.e., TiO 2 , Al 2 O 3 , Ta 2 O 3 , and HfO 2 .…”
Section: Materials Selection and Experimental Guidancementioning
confidence: 99%
“…This effect is based on interaction of silicon with laser light. Details about the internal photoelectric effect can be found in [2], [3].…”
Section: Motivationmentioning
confidence: 99%
“…Hence, all attacks have been performed through the front-side of the tested chips. Additional details about the optical FI setup can be found in [3].…”
Section: Setup For Optical Fi Attacks At Ihpmentioning
confidence: 99%
See 2 more Smart Citations